Behavioral Science Foundations of Organization Development: A Critique from the Islamic Perspective by Syed Abdul Hamid al-Junaid and Syed Aziz Anwar (American Journal of Islam and Society, 2000)
This article seeks to advance an Islamic perspective on OrganizationDevelopment. Arguing that OD interventions not only seek to instituteplanned change within organizations, but also change individuals, culturesand societies, the authors suggest that OD interventions canbecome useful tools for bringing about comprehensive development insociety. The authors advance an Islamic perspective on OD in the hopeof transforming Muslim organizations and precipitate comprehensivedevelopment of Muslim societies.